Three-Component Condensation for the Construction of Novel Spirooxindoles - Ji, Fei; Sun, Mu; Lv, Mei-fang; Yi, Wen-bin; Cai, Chun (Synthesis, 2013)
A new route for the synthesis of novel spirooxindoles from isocyanides, dialkyl acetylenedicarboxylates, and N-substituted isatylidene derivatives through [3+2] cycloaddition has been developed. This method has several advantages, such as high regioselectivity, high yields, readily available starting materials, and one-pot operations. The synthetic alkyne-containing spirooxindoles could also be used in the selective synthesis of triazole-containing spirocyclic compounds using a copper azide–alkyne cycloaddition (CuAAC) reaction.
Keywords: multicomponent reaction; spirooxindoles; [3+2] cycloaddition; CuAAC reaction; triazoles